Perlindungan Konsumen Data Pribadi Nasabah Bank Syariah Indonesia ditinjau dari POJK Nomor 6/POJK.07/2022 - Amandha Bayu Wiedyasari; Wardah Yuspin (Faculty of Law, University of Mataram, 2024)
This research aims to study and analyze the legal protection of customer personal data of banks reviewed in POJK No. 6/POJK.07/2022 and the case of leakage of customer personal data of Bank Syariah Indonesia viewed in POJK No. 6/POJK.07/2022. The method used is qualitative research with a normative legal approach. The results show that 1) personal data is data about an individual who is identified or can be identified that needs to be protected. From personal data, private information about an individual can be obtained, which needs to be protected by banking institutions as institutions that rely on public trust for their sustainability. The leakage of customer personal data has legal protection for consumers and the public, as outlined in OJK Regulation No. 06/POJK.07/2022 concerning Legal Protection in the Financial Services Sector, aimed at strengthening consumer protection aspects, including the protection of bank customer personal data as financial service consumers. This regulation emphasizes the prohibition of providing consumers' personal data to third parties. This regulation includes rules on legal sanctions for parties that fail to comply with the provisions, such as provisions regarding the prohibition for financial service providers to misuse consumers' personal data or information. Sanctions imposed include administrative sanctions and nominal fines. 2) Cases of leakage of customer data from Bank Syariah Indonesia can be pursued legally for the leakage of customer personal data in banking services against cybercrimes, according to Article 1 of POJK No. 6/POJK.07/2022. PT. Bank Syariah Indonesia must compensate customers for damages caused by system malfunctions and unlawful acts (PMH) according to Article 11 of POJK No. 6/POJK.07/2022 regarding the prohibition of providing consumers' personal data and/or information. Bank Syariah Indonesia must be responsible for the leakage of customer data without the need for proof of fault, as sanctions for data breaches have been regulated in Article 3, paragraph 3, of POJK No. 6/POJK.07/2022.